The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1678-7153.201427207
|View full text |Cite
|
Sign up to set email alerts
|

Análise da Validade e Precisão de Instrumento de Diferencial Semântico

Abstract: ResumoEste estudo investigou evidências de validade e precisão de um instrumento de diferencial semântico que tem sido utilizado para medir a transferência de signifi cados entre estímulos equivalentes. Um total de 196 estudantes universitários avaliou fotografi as de faces expressando emoções e também fi guras abstratas, utilizando um instrumento composto por 13 escalas bipolares ancoradas por adjetivos opostos. A análise fatorial dos dados coletados forneceu indicações da validade do instrumento e os coefi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
7
0
5
Order By: Relevance
“…The scales are listed so as to separate the Factor 1 scales (above the dotted line) from the Factor 2 scales (below the dotted line). Almeida et al (2014) found that Factor 1 scales provided reliable assessment of the affective valence of stimuli (Cronbach's coefficient alpha, 0,91), thus providing data relevant to the aims of the present research. The Factor 2 scales were marginally reliable as measures of potency/activity (Cronbach's coefficient alpha, 0,62) and may be conceived as distractors, since the present study is concerned with valence.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The scales are listed so as to separate the Factor 1 scales (above the dotted line) from the Factor 2 scales (below the dotted line). Almeida et al (2014) found that Factor 1 scales provided reliable assessment of the affective valence of stimuli (Cronbach's coefficient alpha, 0,91), thus providing data relevant to the aims of the present research. The Factor 2 scales were marginally reliable as measures of potency/activity (Cronbach's coefficient alpha, 0,62) and may be conceived as distractors, since the present study is concerned with valence.…”
Section: Resultsmentioning
confidence: 69%
“…Each scale, which comprised seven values, was anchored by two opposite adjectives, and represented steps in a continuum that ranged from one adjective to its opposite. The Semantic Differential as used in this study was validated by a psychometric study reported by Almeida, Bortoloti, Ferreira, Schelini, and de Rose (2014).…”
Section: Setting Equipment and Stimulimentioning
confidence: 99%
“…BOM_1_:_2_:_3_:_4_:_5_:_6_:_7_MAU Cada espaço recebe um valor numérico compreendendo, por exemplo, de 1 a 7, que definirá a direção e a distância do polo, a direção indica a qualidade e a distância a intensidadequanto mais próximo de um polo maior a percepção daquele adjetivo está presente, e quanto mais ao centro maior a ausência da percepção (LOPES et. al., 2011;ALMEIDA et. al., 2014).…”
Section: Materiais E Métodosunclassified
“…Cópias do instrumento validado por Almeida et al (2014) foram entregues aos participantes do Grupo Experimental e do Grupo Controle. O estímulo a ser avaliado ficava na parte superior da folha e as 13 escalas ficaram logo abaixo dele, ocupando toda a posição central da folha.…”
Section: Testesunclassified
“…Na presente pesquisa, as escalas do Fator 1 serão analisadas. De acordo com Almeida et al (2014) As escalas à esquerda da Figura 2 mostram as avaliações feitas dos estímulos da Classe Alegre. As medianas das avaliações do estímulo C1 pelo Grupo Experimental em cada uma das nove escalas do Fator 1 foram as seguintes: "triste-alegre": +1; "tenso-relaxado": +1; "áspero-liso": +2; "feio-bonito": +1,5; "pesado-leve": +1,5; "negativo-positivo": +2; "duro-macio": +0,5; "mau-bom": +2; "desagradável-agradável": +2,5.…”
Section: Análise Dos Diferenciais Semânticosunclassified